Pemanfaatan Sampah Plastik Menjadi Meja Dan Kursi Berbasis Ecobrick Sebagai Program Pemberdayaan Masyarakat Pada KKN Unikal Di Kelurahan Kuripan Yosorejo - M. Sigit Taruna; Amza Setian Naufal; Evi Imania; Muchamad Rusydi; Muchammad. Zidan Dhiya`Ul Haq; M. Sandy Firdaus; Nia Yuliyawati; Pryamitra Agus; Paramita Pratiwi; Putri Sovia Melati; Selvy Liana; Wirdatul Jannah; Zahrina Ghaisani Dhafarina (CV. SINAR HOWUHOWU, 2026)
The problem of plastic waste is becoming an increasingly complex environmental issue, especially in densely populated areas. Kuripan Yosorejo Village is one area that still faces limitations in managing household plastic waste. Through the Community Service Program (KKN) at the University of Pekalongan (UNIKAL), a community empowerment program was conducted to utilize plastic waste to create furniture products, including ecobrick-based tables and chairs. The implementation method included socialization of household-based waste management through the application of the 3Rs, ecobrick-making training, and hands-on table and chair assembly with the community. This activity involved the active participation of residents, particularly women from the Family Welfare Movement (PKK) and local youth. The results showed that the community gained increased knowledge and skills in processing plastic waste into useful products. In addition to contributing to reducing the volume of plastic waste, this program also produced simple furniture products that can be used for community social activities. This ecobrick utilization program is expected to provide an alternative solution for sustainable plastic waste management and raise public awareness of the importance of environmental conservation.